2018
DOI: 10.4269/ajtmh.18-0342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotics on Short-Term Growth among Children in Burkina Faso: A Randomized Trial

Abstract: Antibiotics improve both weight and height gain in randomized trials of preschool children with preexisting morbidity. Here, we assess the effect of a short course of three different antibiotics (amoxicillin, azithromycin, and cotrimoxazole) on short-term linear and ponderal growth in a population-based sample of preschool children in rural Burkina Faso. We randomized households with at least two children in the Nouna district, Burkina Faso, to a 5-day course of amoxicillin, azithromycin, cotrimoxazole, or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Of these 58 children, >95% of their cohabiting siblings finished their respective treatment course. 12 Approximately two-thirds of enrolled children were female and the median age was 20 months (Table 1 ). Resistance genetic determinants to multiple classes of antibiotics were common in the gut, particularly tetracyclines, trimethoprim and beta-lactams (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of these 58 children, >95% of their cohabiting siblings finished their respective treatment course. 12 Approximately two-thirds of enrolled children were female and the median age was 20 months (Table 1 ). Resistance genetic determinants to multiple classes of antibiotics were common in the gut, particularly tetracyclines, trimethoprim and beta-lactams (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the trial, 165 households were assessed for eligibility and 41 were excluded because two children were not present in the household. The remaining 124 households were eligible for inclusion and were enrolled in the study 11. A total of 248 children were enrolled in the study, of whom 233 had eligible anthropometric measurements at baseline and 4 weeks after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…All treatments were directly observed by study staff and administered as paediatric oral suspension. Children were followed for 35 days from enrolment for anthropometric outcomes 11. All data were collected and managed in CommCare (Dimagi, Cambridge, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a randomized controlled trial in 2 rural communities of the Nouna Health and Demographic Surveillance System [ 9 ]. Detailed methods for the study have been reported elsewhere [ 2 , 10 ]. The study took place in July 2017, at the beginning of the annual rainy season.…”
Section: Methodsmentioning
confidence: 99%